Perancangan dan Pengembangan Sistem Pencatatan Akuntansi Berbasis Website pada Salon Fas - Daniel Apdianto Herman; Andy Kho (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Limited resources, especially human resources in MSMEs, making business owners have to do accounting records manually which will have an impact on inaccuracy in decision making. Therefore, in this research, the author will design and develop an accounting record system for Salon Fas. The method used in this research is the waterfall method, which consists of stages of analysis, design, development, testing, and maintenance. The result of this research is a website-based accounting record system that can manage the accounting needs of Salon Fas. With this system, hopefully that Salon Fas' accounting records will become more easier, accurate, and efficient